2012
DOI: 10.1155/2012/304868
|View full text |Cite
|
Sign up to set email alerts
|

Hopf Bifurcation in an SEIDQV Worm Propagation Model with Quarantine Strategy

Abstract: Worms exploiting zero-day vulnerabilities have drawn significant attention owing to their enormous threats to the Internet. In general, users may immunize their computers with countermeasures in exposed and infectious state, which may take a period of time. Through theoretical analysis, time delay may lead to Hopf bifurcation phenomenon so that the worm propagation system will be unstable and uncontrollable. In view of the above factors, a quarantine strategy is thus proposed in the study. In real network, unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…If = 0 , then ± 0 is a pair of purely imaginary roots of (12). Moreover, if the conditions in Lemma 3.4 (1) in [14] are satisfied, then…”
Section: Lemmamentioning
confidence: 99%
See 1 more Smart Citation
“…If = 0 , then ± 0 is a pair of purely imaginary roots of (12). Moreover, if the conditions in Lemma 3.4 (1) in [14] are satisfied, then…”
Section: Lemmamentioning
confidence: 99%
“…Some research achievements [10][11][12] showed that the spread dynamic system of malware would be unstable and bifurcation and chaos would appear. Considering the fact that the intrusion detection system (IDS) may lead to time delay, Yao et al [13][14][15] obtained the threshold of time delay when Hopf bifurcation occurred. Pulse quarantine strategy [16] also has been taken to constrain the propagation of worms in network.…”
Section: Introductionmentioning
confidence: 99%
“…As far as we know, the use of quarantine strategies has produced a great effect on controlling disease. People use quarantine strategies widely in worm containment enlightened by this [10][11][12][13][14][15][16]. In addition, some scholars have done research on time delay [17][18][19].…”
Section: Related Workmentioning
confidence: 99%
“…Yao et al research the worm propagation model by considering the time delay [28]. They found that time delay may lead to Hopf bifurcation phenomenon which will make the worm propagation system unstable and uncontrollable.…”
Section: Related Workmentioning
confidence: 99%